The Roles Of English In Tourism Development At Pengkelak Mas Tourism Village - Fina Islami; Ari Prasetyaningrum; Siti Maysuroh; Laila Wati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This study explored the perceptions of stakeholders towards English proficiency in Pengkelak Mas tourism village. Four research questions were set to lead the study; (1) English roles in developing Service satisfaction, (2) challenges stakeholder face in developing Pengkelak Mas tourism village, (3) factors contributing to the challenges in developing English proficiency in Pengkelak Mas tourism village and (4) solution can be implemented to solve the problem of increasing English ability in developing Pengkelak Mas tourism village. Qualitative descriptive was used to determine the research result. Documentation, observation, questionnaire and interview were used to obtain the data. The data was analyzed by thematic analysis with 17 participants from different background chosen through random technique. The results depicted that stakeholders agree that English is important for their professional life as it increase the work efficiency, as well as the challenges faced by stakeholders in developing tourism in Pengkelak Mas village include a lack of English proficiency. The absence of language training facilities constituted one of the factors. Therefore, a feasible solution to address this issue is the establishment of specialized English language training focusing on the context of tourism.